1999
DOI: 10.1152/ajpregu.1999.276.4.r1010
|View full text |Cite
|
Sign up to set email alerts
|

Central and peripheral administration of endothelin-1 induces an increase in blood pressure in conscious trout

Abstract: The central and peripheral cardiovascular effects of endothelin (ET)-1 and ET-3 were investigated in conscious rainbow trout. Both intracerebroventricular and intra-arterial injections of ET-1 (6.25–25 pmol) but not ET-3 (25 pmol) caused a dose-dependent increase in mean dorsal aortic blood pressure and a concomitant decrease in heart rate. The hypertensive effects induced by intra-arterial and intracerebroventricular injection of ET-1 were associated with a significant ( P < 0.05) increase in systemic vasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
1
9
1
Order By: Relevance
“…Furthermore, hypercortisolemia has related with elevated ET-1 levels (Lederbogen et al 1999). The current data disagree with (le Mevel et al 1999) demonstrated that intraarterial injection of ET-1 did not markedly modify cortisol levels. Also, (Vierhapper et al 1995) concluded that cortisol concentration was unchanged by infusion of ET-1.…”
Section: Discussioncontrasting
confidence: 93%
“…Furthermore, hypercortisolemia has related with elevated ET-1 levels (Lederbogen et al 1999). The current data disagree with (le Mevel et al 1999) demonstrated that intraarterial injection of ET-1 did not markedly modify cortisol levels. Also, (Vierhapper et al 1995) concluded that cortisol concentration was unchanged by infusion of ET-1.…”
Section: Discussioncontrasting
confidence: 93%
“…The cannula was immediately flushed with 60 l of vehicle (0.9% NaCl). The ET-1 solution was freshly prepared from a stock solution (10 Ϫ4 M), and the dose was chosen from the dose-response curves reported in the literature (28,56). Triton X-100 was added to prevent the adsorption of ET-1 to the tube wall.…”
Section: Methodsmentioning
confidence: 99%
“…The potent hemodynamic effects of endothelin-1, such as increase in blood pressure (37,35), could also be important in vivo. In previous studies with the teleost rainbow trout, endothelin-1 has been found to cause several short-term oscillations in blood pressure followed by a sustained hypertensive period (19,15,6). In mammals, it has been found that locally induced vasoactive agents, such as endothelin-1, mediate, in a paracrine fashion, part of the stretch-induced ANP secretion (29).…”
Section: Discussionmentioning
confidence: 98%